Reports of the 11th century Andalusian Geographer on the Peoples of Caucasus - Magomed A. Gizbulaev (RUDN Journal of World History, 2023)
This paper, for the first time in Russian historiography, provides information on the 6th-10th centuries history of Dagestan on the basis of translation, commentary and comparative analysis of excerpts in relation to the history of Caucasian peoples from AbūʿUbayd al-Bakrī’s (d.1094) Kitāb al-masālik wa-al-mamālik (A Book of Routes and Countries). This work presents a brief description of different polities: indicating trade routes, distances between towns etc. sort of the administrative directory. Kitāb al-masālik wa-al-mamālik is considered as one of the important sources on south-western and north-western Africa history, particularly, during the period of the Almoravids’ reign (1040-1147). As for the information about the Caucasus given by al-Bakri so it’s largely not original. The paper discusses the main aspects of al-Bakrī’s life and scholarly activities who was an expert in Islamic history and Arabic geography. He particularly outlines the history of different Caucasian polities like Derbent; describes the Caspian sea; gives detailed list of routes and distance between polities etc. Moreover, I compared some reports on Dagestan from Muruj az-zahab and Kitab at-tanbih by al-Mas‘udi and al-Bakrī’s work in order to find out whether the origin of the material is the same.